Digitalizing History: Development of E-Module for History Learning on the Subject of Japanese Colonialism Period in Indonesia - Muhammad Reza Arviansyah; Sani Safitri; Syarifuddin Syarifuddin; Alfiandra Alfiandra (JINoP (Jurnal Inovasi Pembelajaran), 2024)
This study aims to investigate the effectiveness of using e-module teaching materials in history education. This study is development research conducted using direct observation techniques and the distribution of questionnaire surveys to the research location, in this case, SMA Srijaya Negara Palembang. The development of teaching materials was conducted using the Rowntree model, which comprises three stages: planning, development, and evaluation. The criteria utilized included the success rate and students’ achievement in learning activities. The research findings indicate that the utilization of case-based learning e-modules is valid and suitable for history education in classrooms. This is supported by assessments from three validators of the materials, media and language aspects of the e-module, categorized as highly valid (4.4); individual assessments as valid (4.1); and small group assessments as highly valid (4.2). Moreover, there is a noticeable improvement in the students’ learning outcomes, classified as valid (88.0), with an effectiveness score of N-gain reaching 0.80, falling into the high or very effective category.